Vocabulário técnico e formação dos profissionais da área têxtil: necessidade, elaboração e avaliação de um dicionário de terminologia do vestuário - Felipe, Maria Gorete (2007)
This research work deals with the compilation of a dictionary on clothing terminology intended to be used as a pedagogic tool as part of the teaching and learning process in the Textile Engineering Course at the Federal University of Rio Grande do Norte. The main terms were selected and assessed by a team of textile teachers and students with the objective to be structured as a conceptual body of information on the following sub-areas of clothing terminology: materials (fabrics and trimmings) and products (garments). This research comprises three main steps: (a) characterization and understanding of the technical vocabulary in the clothing area as well as the identification of a pedagogic demand for a dictionary on clothing terminology, clearly expressed by the textile lecturers and students involved in the assessment of the need and validation of this project development; (b) a proposal for a specific methodology for the compilation of the dictionary which could help the communication process in the lecturing of clothing terminology and (c) based on the terminological principles and the technique of focal groups the dictionary was assessed. The technique of focal groups was used in the first step. In the second step the technique used was that of the terminological methodology adapted to the teaching approach in the Textile Course. In the third step the technique of focal groups was again utilized. It was observed that the main concern of lecturers and students is the lack of a standardized vocabulary, which renders difficult the communication process in both the teaching and learning activities as well as the professional ones in the textile industries. Various aspects, which can overlap, cause this lack of standardization. The main ones pointed out by the study team in the focal groups are: usage of regional words or expressions, usage of foreign words or expressions, analogies, and the low level of formal education, mainly among the industry workers. Another aspect to be considered is the lack of textile literature written in the Portuguese language of Brazil. This evidence shows the importance of a clothing terminology dictionary which will benefit both the education and professional activties in this field of knowledge. This dictionary will also give a substantial contribution to terminological standardization in our research field. With view to fulfill this demand, a dictionary of clothing terminology was compiled with 760 main entries, according to the modern practice in terminology with the necessary modifications concerning our needs. The result of the dictionary assessment was very assertive regarding its structure, contents and possible use in various contexts. The team work emphasized their contribution to the standardization process of the terms that proved to be one of the most important and difficult aspects of this researh work. The significance of this structured terminological dictionary was confirmed by the focal group participants relating to its use for teaching and learning activities, as a reference book, as a source of technical information and also as a tool for pedagogic studies and planning, as well as a significant collaboration to the pedagogic practices in the textile engineering course at University or any other educational institution. Besides, this dictionary can also be used to supply information within the textile field. We are aware that the present work will not exhaust the objectives of this research due to its limitations in opposition to the vast complexity demanded by the compilation of a complete work including all the areas and sub-areas of textile engineering. However, it is an important source for dissemination of concepts on the field of clothing terminology and a tool to effective standardization of the terms used in this subject field